Foucault and Power: A Critique and Retheorization. Issue 3 (2nd October 2022) - Haugaard, Mark
ABSTRACT: From the perspective of sociological theory, Foucault's concepts of power, power-knowledge, and discipline are one-sided. While Foucault contends that there is no center of power, his account of power remains top-down or structural, missing the interactive and enabling aspects of power. A more balanced view would suggest that all exercises of power include meaningful agency (the ability to do something); social structures (not simply as constraints but as interactive creations); social knowledge (including both reifying truth claims and enabling truth or knowledge); and social-ontological being-in-the-social-world (both as enabling and dominating).